Catching Audiovisual Interactions With a First-Person Fisherman Video Game. (July 2017) - Sun, Yile; Hickey, Timothy J.; Shinn-Cunningham, Barbara; Sekuler, Robert
The human brain is excellent at integrating information from different sources across multiple sensory modalities. To examine one particularly important form of multisensory interaction, we manipulated the temporal correlation between visual and auditory stimuli in a first-person fisherman video game. Subjects saw rapidly swimming fish whose size oscillated, either at 6 or 8 Hz. Subjects categorized each fish according to its rate of size oscillation, while trying to ignore a concurrent broadband sound seemingly emitted by the fish. In three experiments, categorization was faster and more accurate when the rate at which a fish oscillated in size matched the rate at which the accompanying, task-irrelevant sound was amplitude modulated. Control conditions showed that the difference between responses to matched and mismatched audiovisual signals reflected a performance gain in the matched condition, rather than a cost from the mismatched condition. The performance advantage with matched audiovisual signals was remarkably robust over changes in task demands between experiments. Performance with matched or unmatched audiovisual signals improved over successive trials at about the same rate, emblematic of perceptual learning in which visual oscillation rate becomes more discriminable with experience. Finally, analysis at the level of individual subjects' performance pointed to differences in the rates at which subjects can extract information from audiovisual stimuli.